Stress And Its Effects - Duschanova Sarajon Yuldoshevna (Global Scientific Publishing, 2022)
the article describes the concept of stress that occurs in personal activity, its negative effects on human mental and medical health, its consequences, the factors of identifying and eliminating harmful stress factors.
Keywords: stress; grief; functional states